INFORMAL LEARNING AND NONFORMAL EDUCATION IN RANTE LIMBONG COMMUNITY - Amir Patintingan; Elihami Elihami; Mustakim Mustakim; Nurisan Lateh (Universitas Muhammadiyah Enrekang, 2019)
The purpose of this research is to revolutionize the mentality of the Lembang community / Rante Liombong Villagem motivate and stimulate the work spirit of the Lembang / Rante Liombong Village community and the character of the community must act for change in a better direction. The target of this study is to become a community of integrity, willing to work hard, and have a mutual cooperation spirit.